Anesthetic efficacy of propofol combined butorphanol in laparoscopic surgery for ectopic pregnancy: A protocol of systematic review and meta-analysis. Issue 20 (15th May 2020) - Chang, Wang-yan; Li, Hai-ying
Abstract: Background: Recent studies have suggested that propofol combined butorphanol (PB) has anesthetic effect in laparoscopic surgery (LS) for ectopic pregnancy (EP). But investigations of its potential effects are inconsistent. We will explore the current literature examining PB in LS for EP. Methods: We will perform a comprehensive search from MEDLINE, Embase, Cochrane Library, PsycINFO, Global Health, Web of Science, Allied and Complementary Medicine Database, and China National Knowledge Infrastructure from inception to the present. Other literatures, such as conference abstracts, references to the relevant reviews will also be checked. Two authors will check the titles, abstracts, and full texts independently. They will also independently carry out data collection and study quality assessment. We will conduct statistical analysis using RevMan 5.3 software. Results: This study will provide accurate results on the anesthetic effect and safety of PB in LS for EP. Conclusion: This study will establish high-quality evidence of the anesthetic effect and safety of PB in LS for EP to facilitate the clinical practice and guideline development. Study registration number: INPLASY202040044.